AFFORDABLE HOUSING IN PAKISTAN: A COMPARISON BETWEEN LANDED AND VERTICAL HOUSING DEVELOPMENT IN LAHORE - Rehman, Abdul; Tedong, Peter Aning; Md Dali, Melasutra (International Journal of Property Sciences (E-ISSN: 2229-8568), 2024)
Pakistan has experienced substantial housing growth and stands as one of the most urbanised countries in South Asia, yet it grapples with a housing backlog exceeding 10 million units. The affordability challenges in Lahore are particularly acute. In the realm of affordable housing, there is a preference for vertical living over landed homes. However, no prior research has systematically examined the price correlation between apartment living and landed housing, along with the impact of policies in the context of neoliberal ideology within Pakistan. Neoliberalism, emphasising the superiority of the market over the state has been a dominant force influencing affordable housing strategies. With this backdrop of affordability and neoliberalism, this paper aims to examine the performance difference between landed and vertical housing development. This paper aims to draw an affordability comparison between landed and vertical housing development using a document review and market survey. The study used a qualitative approach employing a case study design. For the data collection, interpretative discourse analysis for public documents was performed, and field surveys for pricing evaluation were conducted in Lahore. The analysis revealed that apartments by the private sector are not affordable for low-income people, often characterised by larger sizes and lacking specific quotas for low-income residents. The study recommends a comprehensive review of building regulations, particularly focusing on specific provisions (quota) targeting low-income people in housing development.